Peningkatan Hasil Belajar PAK Melalui PBL Berbantuan Multimedia Materi Dialog Kelas XII IPA SMA Xaverius Lubuklinggau - Ngadikir Ngadikir (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is a fundamental pillar in nation-building, and continuous efforts are required to enhance the quality of education. The Merdeka Curriculum, implemented in Indonesia, includes Catholic Religious Education and Character Education. However, SMA Xaverius Lubuklinggau faces challenges in improving students' learning outcomes in these subjects, particularly in Phase F of Grade XII in the Science Program. The issues are related to character and academic achievements. This research proposes a solution by implementing the Problem-Based Learning (PBL) model assisted by multimedia. The aim of the study is to evaluate the improvement of students' learning outcomes in the aspects of faithful attitude and academic achievement. Through classroom action research with two cycles using tests and observations as data collection techniques, the results indicate that the PBL model assisted by multimedia is effective in enhancing students' learning outcomes. Focusing on the Dialog and Cooperation Among Religious Communities material, this research contributes to a deeper understanding of how innovative approaches can improve the quality of education, particularly in the context of Catholic Religious Education and Character Education at SMA Xaverius Lubuklinggau.